Market entry strategy in the presence of market spillovers and efficiency differentiation. (12th March 2021) - Wu, Xiangxiang; Zha, Yong; Li, Linzi; Yu, Yugang
Abstract: Firms form various alliances or use brand extensions to enter new markets in order to improve their operational efficiency and create a positive spillover. However, they do not always know the implications of these strategies for market entry and multimarket competition because the sale of products in one market can have negative spillover effects on product sales in other markets. We present an analytical framework to examine whether and how (i.e., by choosing alliance entry or independent entry) competing firms should enter a market in a situation where market spillovers occur when a firm enters a spillover‐producing market to sell products that may increase or decrease the consumers' willingness to pay for products in the primary market. Our analysis shows that the operational efficiency (or quality differentiation ability) of firms in a spillover‐producing market varies, and hence, the impact of market spillovers differs for firms. We identify the key factors, such as bargaining power, brand value difference in the primary market, and the extent of efficiencies and spillovers, that determine the firms benefitting from the different entry strategies. Specifically, we show that firms would be more willing to choose an alliance strategy to enter a spillover‐producing market if the negative spillover is small and alliance efficiency is high. In contrast, if an alliance entry is not favored, the firms' relative operational efficiency is crucial for them to decide whether to enter the market independently under moderate spillover conditions. Finally, we show the implications of market entry strategies for managers.